The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40516-015-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Laser-arc Welding of 17-4 PH Martensitic Stainless Steel

Abstract: 17-4 PH stainless steel has wide applications in severe working conditions due to its combination of good corrosion resistance and high strength. The weldability of 17-4 PH stainless steel is challenging. In this work, hybrid laser-arc welding was developed to weld 17-4 PH stainless steel. This method was chosen based on its advantages, such as deep weld penetration, less filler materials, and high welding speed. The 17-4 PH stainless steel plates with a thickness of 19 mm were successfully welded in a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…The base metal used in this study was 17-4 PH martensitic SS H1150 which has the density of 7820 kg/m 3 Table 1 [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The base metal used in this study was 17-4 PH martensitic SS H1150 which has the density of 7820 kg/m 3 Table 1 [9].…”
Section: Methodsmentioning
confidence: 99%
“…The weldability of 17-4 PH martensitic SS is good for the traditional arc welding processes, such as gas tungsten arc welding (GTAW) [7], and shielded metal arc welding (SMAW) [8]. It is reported that welding of thick 17-4 PH martensitic SS plates is typically done in an overaged condition in order to reduce the crack susceptibility [9]. Das et al [10] studied the GTA welding of 12 mm thick 17-4 PH SS plates in a single bevel groove configuration where the overaging was done at 621 °C.…”
Section: Introductionmentioning
confidence: 99%
“…As it was previously noted, the authors [16] found that the speed and depth of the melted through material non-linearly depend on each other, for example at the speed of 30 mm/s the depth of melted through material is 13.6 mm, at the speed of 20 mm/s the depth is 14.8 mm, at the speed of 10 mm/s the depth is 16.1 mm. For studying of this phenomenon in the case of the defocused beam a test was performed on melting of the continuous sheet by the defocused beam (+20 mm) at different welding speeds (Fig.…”
Section: Methodsmentioning
confidence: 63%
“…The authors [16] study weldability of 17-4 PH martensitic stainless steel, and the following facts were found out: the welding speed does not have significant effect on the depth of the melted through material, but significantly affects formation of pores (10 mm/s, 20 mm/s, 30 mm/s), i.e. the higher the speed the less pores.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, however, there are technological solutions that reduce hardness of the weld joints during the welding process, such as defocused laser beam welding, bifocal beam, or laser-arc welding. The authors [18] use two-pass method or heat treatment of the whole weld for reducing hardness of the welded joint obtained by laser-arc welding of martensitic steel. Two-pass method can reduce the temperature of preheating by 100°C; the authors note that, in laser welding of large thickness, there is high hardness of the weld root side in Electronic supplementary material The online version of this article (doi:10.1007/s00170-015-7312-y) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%